2018
DOI: 10.1016/j.janxdis.2018.01.004
|View full text |Cite
|
Sign up to set email alerts
|

ICD-11 complex PTSD among Israeli male perpetrators of intimate partner violence: Construct validity and risk factors

Abstract: The International Classification of Diseases 11th Version (ICD-11) will include Complex Posttraumatic Stress Disorder (CPTSD) as a unique diagnostic entity comprising core PTSD and DSO (disturbances in self-organization) symptoms. The current study had three aims: (1) assessing the validity of CPTSD in a unique population of male perpetrators of intimate partner violence; (2) examining whether exposure to different types of traumatic events would be associated with the two proposed CPTSD factors, namely PTSD o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 40 publications
(71 reference statements)
4
56
0
3
Order By: Relevance
“…Cumulative childhood trauma and physical neglect predicted membership to the CPTSD class as compared to the low symptom class. This finding is consistent with research suggesting that interpersonal victimisation represents a key risk factor for the development of CPTSD (Ben-Ezra et al, 2018;Cloitre et al, 2013;Gilbar et al, 2018;Hyland et al, 2017;Karatzias et al, 2016;Shevlin et al, 2017) and literature illustrating that neglect plays a unique role in the development of psychopathology (e.g. Teicher & Samon, 2016).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Cumulative childhood trauma and physical neglect predicted membership to the CPTSD class as compared to the low symptom class. This finding is consistent with research suggesting that interpersonal victimisation represents a key risk factor for the development of CPTSD (Ben-Ezra et al, 2018;Cloitre et al, 2013;Gilbar et al, 2018;Hyland et al, 2017;Karatzias et al, 2016;Shevlin et al, 2017) and literature illustrating that neglect plays a unique role in the development of psychopathology (e.g. Teicher & Samon, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…ICD-11 CPTSD has been found to manifest following sustained interpersonal trauma exposure and cumulative trauma exposure in a dose-response manner, with trauma occurring during developmental periods creating a particular vulnerability (Ben-Ezra et al, 2018;Cloitre, Garvert, Brewin, Bryant, & Maercker, 2013;Gilbar, Hyland, Cloitre, & Dekel, 2018;Hyland et al, 2017;Karatzias et al, 2016;Maercker, Hecker, Augsburger, & Kliem, 2018;Shevlin et al, 2017). Literature concerning the prevalence of sexual violence consistently indicates that victimisation is likely to begin during early development (Basile & Smith, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research indicated that depression was more strongly related to the DSO symptoms and CPTSD (Gilbar et al, 2018;Hyland, Shevlin, Fyvie, & Karatzias, 2018b;Nemčić-Moro et al, 2011) while anxiety disorders were more strongly related to PTSD (Hyland et al, 2016). Other studies revealed an essentially equivalent association of anxiety to the PTSD and DSO clusters of symptoms (Gilbar et al, 2018;Karatzias et al, 2016). These confounding results emphasize the need for further work in exploring the relationship between PTSD and CPTSD, as well as other psychiatric disorders particularly depression and anxiety.…”
Section: Discussionmentioning
confidence: 92%
“…The prevalence of the current comorbid disorders was similar in the PTSD and the CPTSD group, with the exception of GAD, which was significantly more likely to be present in the CPTSD group. Previous research indicated that depression was more strongly related to the DSO symptoms and CPTSD (Gilbar et al, 2018;Hyland, Shevlin, Fyvie, & Karatzias, 2018b;Nemčić-Moro et al, 2011) while anxiety disorders were more strongly related to PTSD (Hyland et al, 2016). Other studies revealed an essentially equivalent association of anxiety to the PTSD and DSO clusters of symptoms (Gilbar et al, 2018;Karatzias et al, 2016).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation